2016
DOI: 10.1074/jbc.m116.760447
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Phosphate Starvation-induced Wall Teichoic Acid Hydrolases Provides First Insights into the Degradative Pathway of a Key Bacterial Cell Wall Component

Abstract: The cell wall of most Gram-positive bacteria contains equal amounts of peptidoglycan and the phosphate-rich glycopolymer wall teichoic acid (WTA). During phosphate-limited growth of the Gram-positive model organism Bacillus subtilis 168, WTA is lost from the cell wall in a response mediated by the PhoPR two-component system, which regulates genes involved in phosphate conservation and acquisition. It has been thought that WTA provides a phosphate source to sustain growth during starvation conditions; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 64 publications
1
49
0
Order By: Relevance
“…Together these changes reduce the cellular requirement for phosphate while maintaining the anionic character of the cell wall. Recently Myers and colleagues () reported that PhoPR regulon genes phoD and glpQ encode enzymes that cleave poly(glycerol phosphate) endo‐ and exo‐lytically respectively, thereby revealing a capability to recycle and reutilize the phosphorous content of cell wall material that is released during growth. Thus, WTA serves as a phosphorous store that can be mobilized under conditions of limitation (Myers et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Together these changes reduce the cellular requirement for phosphate while maintaining the anionic character of the cell wall. Recently Myers and colleagues () reported that PhoPR regulon genes phoD and glpQ encode enzymes that cleave poly(glycerol phosphate) endo‐ and exo‐lytically respectively, thereby revealing a capability to recycle and reutilize the phosphorous content of cell wall material that is released during growth. Thus, WTA serves as a phosphorous store that can be mobilized under conditions of limitation (Myers et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…GlpQ of B. subtilis and orthologs from other bacteria have been shown previously to specifically release Gro3P from GPC, glycerophosphoethanolamine, glycerophosphoglycerol, and bis(glycerophospho) glycerol. For the latter two substrates, K M and k cat values of 1.0 mM and 1275 min −1 , respectively 1.4 mM and 1517 min −1 , were determined for B. subtilis GlpQ (41,45,47). We confirmed the stereospecificity of recombinantly expressed, B. subtilis GlpQ for sn -glycero-3-phosphoryl substrates and determined the enzyme’s stability and catalytic optima, using sn -glycero-3-phosphocholine (GPC) as substrate (Supporting Information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides synthesis, also the turnover of WTA and LTA needs to be differentially regulated, which so far has not been explored in much detail. Recently, the exo-acting sn -glycero-3-phosphate phosphodiesterase GlpQ, along with an endo-acting phosphodiesterase PhoD, has been implicated in the degradation of WTA during phosphate starvation (41). However, apart from WTA degradation during adaptation to phosphate starvation, turnover of WTA likely occurs also along with the turnover of PGN of the cell wall in B. subtilis and other Gram-positive bacteria (4244).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations